Aggresome-autophagy involvement in a sarcopenic patient with rigid spine syndrome and a p.C150R mutation in FHL1 gene - Patrizia eSabatelli; Patrizia eSabatelli; Silvia eCastagnaro; Francesca eTagliavini; Francesca eTagliavini; Martina eChrisam; Francesca eSardone; Francesca eSardone; Laurence eDemay; Pascale eRichard; Spartaco eSanti; Spartaco eSanti; et al. (Frontiers in Aging Neuroscience, 2014)
The four-and-half LIM domain protein 1 (FHL1) is highly expressed in skeletal and cardiac muscle. Mutations of the FHL1 gene have been associated with diverse chronic myopathies including reducing body myopathy (RBM), rigid spine syndrome, and Emery-Dreifuss muscular dystrophy. We investigated a family with a mutation (p.C150R) in the second LIM domain of FHL1. In this family, a brother and a sister were affected by rigid spine syndrome, and their mother had a mild lower limbs weakness. The 34-year-old female had an early and progressive rigidity of the cervical spine and severe respiratory insufficiency. Muscle mass evaluated by DXA was markedly reduced, while fat mass was increased to 40%. CT scan showed an almost complete substitution of muscle by fibro-adipose tissue. Muscle biopsy showed accumulation of FHL1 throughout the cytoplasm and around myonuclei into multiproteic aggregates with aggresome/autophagy features as indicated by ubiquitin, p62 and LC3 labeling. DNA deposits, not associated with nuclear lamina components and histones, were also detected into the aggregates, suggesting nuclear degradation. Ultrastructural analysis showed the presence of dysmorphic nuclei, accumulation of tubulofilamentous and granular material and perinuclear accumulation of autophagic vacuoles. These data point to an involvement of the aggresome-autophagy pathway in the pathophysiological mechanism underlying the muscle pathology of FHL1 C150R mutation.